Fundamentals of vibration analysis - Myklestad, Nils O. (New York : Dover Publication, Inc., 2018)
This concise textbook discusses vibration problems in engineering, dealing with systems of one and more than one degrees of freedom. A substantial section of Answers to Problems is included. 1956 edition
Chapter 1. Fundamentals -- Chapter 2. Undamped Vibrations of single-degree of freedom systems -- Chapter 3. Vibrations of Single degree of freedom systems of damping -- Chapter 4. Systems of One Degree of freedom with Nonviscous Damping -- Chapter 5. Undamped Vibrations of systems with More than One Degree of freedom -- Chapter 6. Application of generalized coordinates -- Chapter 7. Damped Vibrations of systems with more than one degree of freedom -- Chapter 8. Tabular Methods for finding natural frequencies.
Includes index.
Keywords: VIBRATION